The European Commission Proposal for a Council Directive on a Common Corporate Tax Base (CCCTB) as an Example of Applying Financial Accounting Standards in Taxation on the Corporate Income Tax - Endrijaitis, Martynas (Teisė, 2021)
This article discloses the conception of CCCTB and the relations between CCCTB and the legal regulation of financial accounting, including an analysis of concrete examples of how financial accounting rules are applied in CCCTB. The research highlights the necessity of applying financial accounting standards in CCCTB.